1997
DOI: 10.1038/bjc.1997.205
|View full text |Cite
|
Sign up to set email alerts
|

Screening for TP53 mutations in patients and tumours from 109 Swedish breast cancer families

Abstract: Summary To estimate the prevalence of TP53 mutations in familial breast cancer, constant denaturant gel electrophoresis (CDGE) was used to screen exons 5-8 of the TP53 gene for germline mutations. Genomic DNA from 128 breast cancer patients belonging to 109 families with familial cancer were screened. No germline mutations were found in any of the patients. We also studied TP53 mutations in tumour DNA from 51 of the same individuals and found mutations in 14%. This is similar to what has been reported in spora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The patient (21NF) showed a novel missense change G5403A (Val97Ile) in exon 4 but nothing in exon 5 replacing one hydrophobic amino acid by another in the transcription activation domain of p53 protein along with protein truncating 4956insG of BRCA1 gene. Our results are in good agreement with Schlichtholz et al [34] and Zelada-Hedman et al [35] who also observed low frequency of germline p53 mutation in familial breast cancer with or without BRCA1 mutation. Thus, apart from Li Fraumeni syndrome [36], p53 gene mutation appears to be of rare occurrence in familial breast cancer with or without BRCA1 mutation and is unlikely to play a major role in breast carcinogenesis.…”
Section: Discussionsupporting
confidence: 93%
“…The patient (21NF) showed a novel missense change G5403A (Val97Ile) in exon 4 but nothing in exon 5 replacing one hydrophobic amino acid by another in the transcription activation domain of p53 protein along with protein truncating 4956insG of BRCA1 gene. Our results are in good agreement with Schlichtholz et al [34] and Zelada-Hedman et al [35] who also observed low frequency of germline p53 mutation in familial breast cancer with or without BRCA1 mutation. Thus, apart from Li Fraumeni syndrome [36], p53 gene mutation appears to be of rare occurrence in familial breast cancer with or without BRCA1 mutation and is unlikely to play a major role in breast carcinogenesis.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, based on its pivotal role in DNA damage repair and its physical and functional interactions with BRCA1 and BRCA2 proteins (Storey et al, 1998), p53 seems to be a strong candidate breast cancer predisposition gene. However, previous analyses of high-risk families of different ethnic background yielded a paucity of germline mutations in p53 gene in familial breast cancer (Zelada-Hedman et al, 1997;Balz et al, 2002).…”
mentioning
confidence: 99%
“…Breast cancer risk increases significantly after the second decade, is very high under the age 31 close to 20%-30% on the basis of the Breast cancer RIsk after Diagnostic GEne Sequencing (BRIDGES) study [37], reaches a peak between 25-35 years, and this does tally with estimates from kindreds [38]. This risk drops after 40 years of age based on the relative frequency of TP53 carriers identified [37,39,40], and cumulative risk reaches a plateau before 60 [35,36,38] [38], these likely suffer from ascertainment and survival bias with many carriers dying from other malignancies at young ages. There is clearly a very high rate of contralateral breast cancer approaching 4%-7% annually and significantly higher than BRCA1 or BRCA2 in those diagnosed aged <35 [41].…”
Section: Cancer Risk Associated With Germline Disease-causing Tp53 Vamentioning
confidence: 99%
“…Breast cancer risk increases significantly after the second decade, is very high under the age 31 close to 20%–30% on the basis of the Breast cancer RIsk after Diagnostic GEne Sequencing (BRIDGES) study [ 37 ], reaches a peak between 25–35 years, and this does tally with estimates from kindreds [ 38 ]. This risk drops after 40 years of age based on the relative frequency of TP53 carriers identified [ 37 , 39 , 40 ], and cumulative risk reaches a plateau before 60 [ 35 , 36 , 38 ]. For instance, of 65 known TP53 carriers with breast cancer in the Genomic Medicine Centre in Manchester 32/65 occurred aged <31 (49%), 24 (37%) occurred aged 31–39, 5 (7.5%) aged 40–44 and only 3/65 (4.5%) over age 45.…”
Section: Cancer Risk Associated With Germline Disease-causing mentioning
confidence: 99%